2017
DOI: 10.1097/gme.0000000000000926
|View full text |Cite
|
Sign up to set email alerts
|

Missing documentation in breast cancer survivors: genitourinary syndrome of menopause

Abstract: Objective Breast cancer survivors often take hormonal treatments to prevent the recurrence of breast cancer, particularly aromatase inhibitors that can worsen the symptoms of genitourinary syndrome of menopause (GSM) such as dyspareunia, dysuria, and urinary incontinence, all of which may adversely affect survivors’ quality of life. Few breast cancer survivors experiencing GSM receive adequate assessment or treatment. Methods In this descriptive study, we reviewed medical records for documented GSM and any t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…We therefore searched the literature on breast cancer survivors, and found recent evidence showing that genitourinary symptoms are rarely assessed or treated in this population, revealing a missed opportunity to improve QoL. 74 In addition to physical discomfort, hormonal changes in survivors with POI are also associated with alterations in libido and arousal. Libido may be affected by the emotional burden of disease and its ongoing sequalae.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore searched the literature on breast cancer survivors, and found recent evidence showing that genitourinary symptoms are rarely assessed or treated in this population, revealing a missed opportunity to improve QoL. 74 In addition to physical discomfort, hormonal changes in survivors with POI are also associated with alterations in libido and arousal. Libido may be affected by the emotional burden of disease and its ongoing sequalae.…”
Section: Resultsmentioning
confidence: 99%
“…5 GSM affects more than 50% of postmenopausal women, and is even more pervasive in the female cancer population. 2,6,7 As breast cancer is often diagnosed after menopause, women with breast cancer may experience GSM prior to diagnosis, and breast cancer treatments may intensify symptoms. Broeckel et al 8 compared women with breast cancer treated with chemotherapy to age-matched controls without cancer, and found that breast cancer patients experienced worse sexual function, with vaginal dryness as one of the most significant predictors of poorer sexual function.…”
mentioning
confidence: 99%
“…A total of 3405 articles were identified, 32 studies were included in the qualitative synthesis, and 17 studies were included in the meta‐analysis (see Figure 1). Our review included seven randomized controlled trials, 14–20 eight cohort studies, 2,12,21–26 and 17 cross‐sectional studies 27–43 . A total of 12,611 women with breast cancer were represented in this systematic review; 10,441 of these women were in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In studies that reported follow‐up time points, the median time postdiagnosis when participants were assessed was 2 years (range: 1 month to 5 years) 2,14,19,21,24,25,29,36,38,40,42 . Of the studies that provided a range of follow‐up time points, all were within 5 years postdiagnosis, 15,32,37,39,43 except two studies 27,35 which followed‐up for 10 years. A total of 14 studies did not indicate the number of years postdiagnosis 12,16–18,20,22,23,26,28,30,31,33,34,41 .…”
Section: Resultsmentioning
confidence: 99%